The Role of A.K. Kazem-Bek in Academic Development of H. Faizkhanov - Mukhetdinov, Damir (Scholarya Demo Journal of Ruby, 2024)
The controversial issues surrounding the relationship between Muhammad Ali Mirza (Aleksandr Kasimovich) Kazem-Bek (1802–1870) and Husain Faizkhanov (1823–1866), including the period of their acquaintance and the depth of their contacts, are the focus of this article. Researchers have long utilized the limited known sources to extract information about this relationship. In this paper, the author focuses primarily on archival documents, particularly the rewritten manuscripts by H. Faizkhanov during his collaboration with the Imperial Academy of Sciences in St. Petersburg. The author also pays significant attention to reconstructing the chronology of H. Faizkhanov’s life during the Kazan period using all available data.By looking at the information in a broader sense, we can disprove some ideas that had been put forward about the part Shihab a-Din Marjani (1818–1889) played in putting M.A. Kazem-Bek and H. Faizkhanov in touch with each other, since this scenario doesn’t fit with the formal timelines in the biographies of any of the people involved. In addition, the available information about M.A. Kazem-Bek’s relationship with H. Faizkhanov supports the assumption that it was M.A. Kazem-Bek who contributed to H. Faizkhanov’s decision to move from Kazan to St. Petersburg in order to start cooperation with the Imperial Academy of Sciences, which, therefore, also refutes the earlier hypothesis that H. Faizkhanov’s move to the capital of the Russian Empire was connected with the forthcoming opening of the Faculty of Oriental Languages at the Imperial University of St. Petersburg.